Exploring phenotypic and genotypic diversity among methicillin-resistant, vancomycin-resistant, and sensitive Staphylococcus aureus - Bakeer, Walid; Gaafar, Marwa; El-Gendy, Ahmed O.; El Badry, M. A.; Alblwi, Noaf Abdullah N.; Selim, Heba M. R. M.; Alharbi, Nada K.; Bendary, Mahmoud M. (Medicine (Baltimore), 2024)
Background: Methicillin-Resistant Staphylococcus aureus (MRSA) is a global concern owing to the increasing prevalence of multidrug-resistant (MDR) strains. Vancomycin has been the primary treatment for MRSA; however, Vancomycin-resistant strains are being increasingly reported worldwide. Therefore, comparative studies are essential to support antimicrobial stewardship and improving clinical management. Ultimately, the findings from this study are expected to inform treatment strategies and guide public health interventions effectively. Material and methods: This study investigated the prevalence, antimicrobial resistance, and virulence characteristics of Vancomycin-sensitive S. aureus (VSSA) and Vancomycin-resistant S. aureus (VRSA) within MRSA strains. By employing a combination of phenotypic methods, such as antimicrobial susceptibility testing, and genotypic techniques, including molecular typing and identification of virulence genes, we obtained comprehensive insights into VRSA and VSSA profiles. Results: Of 250 clinical samples, 62 (24.8%) were S. aureus and 27 (43.5%) were identified as MRSA. All MRSA isolates exhibited MDR patterns. Most MRSA strains were VSSA (20/27, 74.1%), while 7 (25.9%) were VRSA. The VRSA isolates showed more antimicrobial resistance than VSSA isolates; however, the VRSA isolates had less virulence than VSSA isolates. Linezolid was the most effective treatment, with a 3.7% resistance rate. A higher percentage of biofilm-producing MRSA (96.3%) was confirmed by both phenotypic and genotypic methods. All isolates, except one VRSA, showed multi-virulence patterns (harbored more than 3 virulence genes). High diversity and low clonality (D-value = 0.99) were found in both VSSA and VRSA. Based on our correlation findings, the emergence of vancomycin resistance could modify the association between antimicrobial resistance and virulence, potentially affecting the pathogenic profile of these strains. The study also revealed complex interactions among host factors (including age and gender), sample origin, antimicrobial resistance, biofilm production, and virulence genes. Conclusion: This study highlights the alarming spread of MRSA and VRSA, which show significant resistance and virulence.